1982
DOI: 10.1128/aac.21.4.575
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin pharmacokinetics in normal and morbidly obese subjects

Abstract: In an uncontrolled study, vancomycin pharmacokinetics were determined in four normal (total body weight [TBW], 65.9 to 89.1 kg) and six morbidly obese (TBW, 111.4 to 226.4 kg) subjects. The morbidly obese subjects were investigated 3 to 4 h after gastric bypass surgery. Mean terminal half-lives, volumes of distribution, and total body clearances for the normal controls and the morbidly obese subjects were 4.8 h, 0.39 liter/kg, and 1.085 ml/min per kg versus 3.2 h, 0.26 liter/kg TBW, and 1.112 ml/min per kg TBW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
72
2

Year Published

1986
1986
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(82 citation statements)
references
References 13 publications
8
72
2
Order By: Relevance
“…Unfortunately, few anti-microbial or other drug dosing guidelines exist for moderately obese individuals, much less for those with super obesity (8). Our patient's vancomycin volume of distribution (131.1 L) was somewhat lower than the urea volume of distribution as calculated using the conventional total body water (0.6 * weight(kg)), Watson (9), or Hume-Meyer formulas (10), though it was consistent with previous findings in obese subjects (11)(12)(13). This discrepancy highlights the limitations of available formulas and suggests that drug dosing strategies may not be substantially different between the obese and super obese.…”
Section: Discussionsupporting
confidence: 72%
“…Unfortunately, few anti-microbial or other drug dosing guidelines exist for moderately obese individuals, much less for those with super obesity (8). Our patient's vancomycin volume of distribution (131.1 L) was somewhat lower than the urea volume of distribution as calculated using the conventional total body water (0.6 * weight(kg)), Watson (9), or Hume-Meyer formulas (10), though it was consistent with previous findings in obese subjects (11)(12)(13). This discrepancy highlights the limitations of available formulas and suggests that drug dosing strategies may not be substantially different between the obese and super obese.…”
Section: Discussionsupporting
confidence: 72%
“…The RIA method [34][35][36][37] had also been employed. Despite the good quality of the analytical results, it is less efficient and more expensive than FPIA, and there is also the disadvantage of using radioactive substances 37 .…”
Section: Immunologic Methodsmentioning
confidence: 99%
“…[42][43][44] del Mar Fernández and others 44 observed that the mean volume of distribution of vancomycin among 46 critically ill patients was 1.69 L/kg, nearly double that observed in healthy adult subjects with normal renal function (0.4-1 L/kg). 30,[45][46][47] In a population-based = area under the concentration-time curve over 24 h, MIC = minimum inhibitory concentration. *MIC was assumed to have a normal distribution, with a range between 0.5 and 2 mg/L and a mean value of 1 mg/L, with 1 million iterations using Monte Carlo simulation.…”
Section: -41mentioning
confidence: 99%